2011
DOI: 10.1155/2011/830952
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Severe Hypocalcemia Secondary to Vitamin D Deficiency in an Elderly Patient

Abstract: Objective. To describe an asymptomatic presentation of severe hypocalcemia secondary to vitamin D deficiency in an elderly patient. Methods. We describe the presentation and clinical course of an elderly woman with asymptomatic severe hypocalcemia referred to an endocrinology clinic for hyperparathyroidism. Results. The patient is an 83-year-old Caucasian woman who presented to an endocrinology clinic for evaluation of hyperparathyroidism, with an intact PTH of 462 pg/mL (normal range 14–72 pg/mL). The same la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
1
1
1
Order By: Relevance
“…Although vitamin D deficiency is known as a cause of hypocalcemia, severe calcium deficiency is rarely reported (31). No difference was observed between the Vit-D groups regarding corrected calcium levels in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…Although vitamin D deficiency is known as a cause of hypocalcemia, severe calcium deficiency is rarely reported (31). No difference was observed between the Vit-D groups regarding corrected calcium levels in our study.…”
Section: Discussioncontrasting
confidence: 69%
“… 2 Vitamin D deficiency, renal failure, and parathyroid hormone deficiency or resistances are the common culprits of hypocalcemia in elderly. 3 5 , 13 A study conducted by Suryanarayana et al found the prevalence of vitamin D deficiency to be 56.3% among elderly ≥ 60 years of age. 14 The activity of renal enzyme, 1-α hydroxylase, is responsible for formation of active vitamin D, which decreases with age leading to vitamin D deficiency and ultimately results hypocalcemia in elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Количество гипокальциемических эпизодов также уменьшается по мере достижения компенсации дефицита/недостаточности витамина D. В нашем исследовании у добровольцев определялась мягкая гипокальциемия, которая не сопровождалась появлением специфических симптомов (судороги, парестезии и др.). Необходимо отметить, что в литературе описаны клинические случаи выраженной гипокальциемии (<2 ммоль/л) на фоне резко сниженного уровня витамина D, которые также не приводили к развитию развернутой клинической картины [18].…”
Section: описание медицинского вмешательстваunclassified